A synopsis of the Tanaidacea (Crustacea: Peracarida) of Singapore, with a review of tanaidacean diversity in Southeast Asia and the South China Sea - Kong, Chim Chee (Zootaxa, 2024)
In the first comprehensive taxonomic study of the tanaidacean fauna of Singapore, a total of 23 species belonging to two suborders, three superfamilies, 13 families and 22 genera were identified from approximately 2,400 specimens, including 11 species that are possibly new to science. This material was collected from various localities in Singapore waters, from the intertidal zone to subtidal habitats up to 91 m in depth. Many species exhibited a narrow bathymetric distribution and strong affiliation to certain habitats or microhabitats such as mudflats, coral reefs, and barnacle shells on rocky shores. The Singapore Strait yielded 20 tanaidacean species, almost thrice the number of species (7) present in the Johor Straits. Three species were confined to the brackish waters in the inner parts of the Johor Straits and Sungei Pandan. Furthermore, a total of 153 tanaidacean species has now been recorded from Southeast Asia and the South China Sea. The presence of the family Numbakullidae in this region is also documented for the first time.